The Bilad al-Sham Conferences: Their Role in The Development of Historical Writing - Jalode, Alian Abdefatah Mohamd (Jordan Journal for History and Archaeology, 2022)
Conferences on the History of Bilad al-Sham have been held at the University of Jordan since the first one in 1974. The conferences examined various topics in the history of Bilad al-Sham through different historical periods, shedding light on various aspects of the political, economic, and social history of Bilad al-Sham, and studying the development of systems and institutions related to Bilad al-Sham across Jordan, Palestine, Syria, and Lebanon. Hundreds of researchers have participated in these conferences, representing various Jordanian and international academic institutions and universities. In addition to the conferences and the publication of their proceedings, the History of Bilad al-Sham Committee has published many specialized studies and analytical indexes related to the history of the Bilad al-Sham in general and the history of Jordan in particular. This paper introduces those conferences and the studies about Bilad al-Sham that have been published, as well as traces the contributions of Jordanian researchers in those conferences and their impact on the development of historical writing about Jordan.